Technology for Development: Ten True Stories Revealing the Complexity of Replicating South Korean Success - Nawaz M. Sharif (STI Policy and Management Journal, 2020)
This essay comprises ten true stories presented to highlight personally observed problematic encountered by Asian developing country leadership who tried to replicate South Korean success in fostering technology innovation induced sustainable economic growth strategy without paying robust attention to the crucial role of creating an "innovation climate/culture" as necessary foundation for myriad development efforts. It seems to Sharif that the country leadership focused too much on the model mechanics, but did not have rigorous concern for the underlying principles of those models. To reveal validity of this assertion, Sharif presents ten true stories that he personally observed. The stories are: (1) True Story on Suspicion and Disrespect; (2) True Story on Mindset Constraint; (3) True Story on Caring for the Weak; (4) True Story of Super Achievers; (5) True Story on Failure to Follow Through; (6) True Story on "Turn Right" into the River; (7) True Story of Motherly Protection; (8) True Story of Supreme Commitment; (9) True Story of KIST and MOST Mirages; and (10) True Story on Plan Implementation.Key words: technology for development, technology innovation, technology management